Posaconazole liquid suspension in solid organ transplant recipients previously treated with voriconazole. Issue 3 (1st June 2015) - Shoham, S.; Ostrander, D.; Marr, K.
Abstract Background Posaconazole (PCZ) has become an attractive alternative to voriconazole (VCZ) in transplant recipients with suspected or proven invasive filamentous fungal infections, causing fewer drug interactions. Here, we describe our experience with PCZ after VCZ in solid organ transplant (SOT) recipients. Methods VCZ was replaced by PCZ liquid solution in 19 SOT recipients (15 lung, 2 kidney, 1 liver, and 1 heart/lung) with invasive pulmonary aspergillosis (12/19; 63.2%), possible invasive pulmonary fungal infection (2/19; 10.5%), prophylaxis (2/19; 10.5%), or pulmonary scedosporiosis, mucormycosis, and mixed fungal species (1 each). Rationales for switch were suspected adverse reactions to VCZ (17/19; 89.4%) and desire to broaden spectrum of coverage to include agents of mucormycosis (3/19; 15.8%). Results PCZ was well tolerated in all patients. In those patients with baseline liver enzyme abnormalities, a median change occurred in concentrations of alanine transaminase (−20 IU/L), aspartate aminotransferase (−17.5 IU/L), and alkaline phosphatase (−61.5 IU/L). Clinical success (resolution, stabilization, or prevention of infection) was achieved in 16/19 (84%) people. Conclusion PCZ appears to have a reasonable safety and tolerability profile and may be an effective alternative in SOT patients who require an agent with anti‐mold activity, but are unable to tolerate VCZ.